Pengabdian KKN Desa Palung Raya Kecamatan Tambang Kabupaten Takalar - Yolanda Safitri; Intan Rahmah Azzahra (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
The Community Service Program (KKN) Behind the Village has been carried out in Palung Raya Village, Tambang District, Kampar Regency. The purpose of this KKN activity is to serve and be directly involved with the community through activities that have been previously designed to be carried out. carried out by collecting data, interviews, outreach to the community. The activities that have been achieved in the implementation of this KKN are (a) additional class activities for elementary school children who are not yet fluent in reading (b) socializing about the importance of literacy, (c) participating in helping the community in selling and promoting MSME products (d) making trash cans from used paint cans.